Pengaruh Motivasi Belajar dan Kegiatan Ekstrakurikuler Sanggar Alquran terhadap Prestasi Belajar Siswa pada Mata Pelajaran Alquran Hadis di Madrasah Aliyah di Kota Manado - Anis Rugaiyah; Rivai Bolotio; Ardianto Ardianto (Journal of Islamic Education Policy, 2017)
ABSTRACT.This study aims to analyze the influence of learning motivation and extracurricular activities of the Qur'an studio either individually (partially) or (simultaneously) to the students' learning achievement on the subjects of Alquran Hadith of Madrasah Aliyah in Manado City. The population in this study was all students of Madrasah Aliyah in Manado City in School Year of 2016/2017 who’s following the extracurricular activities of Alquran studio, which amounts to 300 students. To determine the sample of this research, the researcher uses a table which developed from the formula of Isaac and Michael, which according to the table for a population of 380 people then the sample amounted to 161 people with 5% error rate. The data were collected by using the questionnaire technique. Testing the validity of the questionnaire in terms of construct validity and content validity through expert judgment and content validity by Pearson correlation analysis by using SPSS for Windows Release 20 program. To test the reliability of the questionnaire was analyzed with Alpha-Cronbach. Research hypothesis testing conducted with Multiple Regression, at the real level of 0.05. The process of calculating of the regression test was conducted by using SPSS for Windows Release 20. The results of this research can generally be concluded that: 1) there was significant influence of student's learning motivation on student achievement of Madrasah Aliyah in Manado City inAlquran Hadith subject, 2) there was significant influence of extracurricular activities of Alquranstudio to the students achievement of Madrasah Aliyah in Manado City in Alquran Hadith subject, and 3) there was significant influence of students' learning motivation and extracurricular activities of Alquran studio simultaneously on the students learning achievement of Madrasah Aliyah in Manado City in the subject of Alquran Hadith.. Keywords: Learning Motivation, Extracurricular, Alquran Studio, Learning Achievement ABSTRAK. Penelitian ini bertujuan untuk menganalisis pengaruh motivasi belajar dan kegiatan ekstrakurikuler sanggar Alquran baik secara sendiri-sendiri (parsial) maupun secara bersama-sama (simultan) terhadap prestasi belajar siswa pada mata pelajaran Alquran Hadis di Madrasah Aliyah Kota Manado.Populasi dalam penelitian ini adalah seluruh siswa Madrasah Aliyah yang ada di Kota Manado Tahun Pelajaran 2016/2017 yang mengikuti kegiatan ekstrakurikuler sanggar Alquran, yang berjumlah 300 siswa. Untuk menentukan sampel penelitian, peneliti menggunakan tabel yang dikembangkan dari rumus Isaac dan Michael, dimana berdasarkan tabel tersebut untuk populasi yang berjumlah 300 orang maka sampelnya berjumlah 161 orang dengan taraf kesalahan 5%. Data penelitian dikumpulkan dengan menggunakan teknik angket. Pengujian validitas angket dilihat dari segi validitas konstruk dan validitas isi melalui pertimbangan ahli dan validitas isi melalui analisis korelasi Pearson dengan menggunakan program SPSS for Windows 23. Untuk pengujian reliabilitas angket dilakukan dengan analisis alpha-cronbach. Pengujian hipotesis penelitian dilakukan dengan Regresi Ganda, pada taraf nyata 0,05. Proses penghitungan pengujian regresi menggunakan program SPSS for Windows 23. Hasil penelitian ini secara umum dapat disimpulkan: (1) terdapat pengaruh yang signifikan motivasi belajar siswa terhadap prestasi belajar siswa Madrasah Aliyah di Kota Manado pada mata pelajaran Alquran Hadis, 2) terdapat pengaruh yang signifikan kegiatan ekstrakurikuler sanggar Alquran terhadap prestasi belajar siswa Madrasah Aliyah di Kota Manado pada mata pelajaran Alquran Hadis, dan 3) terdapat pengaruh yang signifikan motivasi belajar siswa dan kegiatan ekstrakurikuler sanggar Alquran secara bersama-sama terhadap prestasi belajar siswa Madrasah Aliyah di Kota Manado dalam mata pelajaran AlquranHadis. Kata kunci: Motivasi Belajar, Ekstrakurikuler, Sanggar Alquran, Prestasi Belajar